Enhanced tunable mid-infrared emissions by controlling rare earth ion energy transfer processes in multifunctional multiphase solids. Issue 12 (September 2021) - Li, Yanchao; Li, Yinyan; Cai, Muzhi; Li, Bingpeng; Huang, Feifei; Lei, Ruoshan; Xu, Shiqing
Abstract: Owing to the increasing application of high-performance and multifunctional mid-infrared (MIR) optoelectronic devices, it is important to achieve a high emission efficiency and broadband tunable luminescence. In this study, nanocrystalline units with unique properties were integrated into an amorphous frame with high transmittance and infinite ductility to achieve an enhanced MIR emission. In the single active ion-doped system, owing to the combination of the lower phonon energy of the crystal, the fixed position of the crystal lattice, and the glass transparency, a substantial increase in the infrared fluorescence intensity was achieved. Particularly, an excellent 3 μm luminescence was realized by the stable composite material. In the co-doped system, a bottom-up strategy was adopted to achieve full coverage of the 2 μm MIR atmospheric window, and the results confirmed that the spatial distribution of the optically active nanocrystal units in the glass frame effectively controlled the energy transfer processes.